Compositions and biological effects of different populations of Cupressus to control adult wheat weevil (Tribolium castaneum Herbst) - Shahla Amini; Hamideh Khalaj; Maryam Ahvazi; Mohammadreza Labbafi (Institue of Medicinal Plants, ACECR, 2023)
Background: Chemical pesticides increasing use caused increased resistance in insects and increases the residue of pesticides in agricultural products and the environment. Objective: The aims of this study was to achieve a safe method and using natural essential oils of Cupressus against adult insects of the wheat flour (Tribolium castaneum Herbst). Methods: A factorial experiment was conducted in a completely randomized design in four replications in 2018. The Cupressus essential oils (EO) Clevenger by water distillation method and measured by GC-MS. Relative growth rate (RGR), repellency and nutritional indicators, and fumigant toxicity of EO on mature Tribolium castaneum Herbst were investigated in 27 ± 1 °C and 65 ± 5 % relative humidity. Results: Alpha-pinene was the major component of the EO in the studied species. The results of the fumigant toxicity test of essential oils showed that increasing concentration and duration of exposure to essential oil caused an increase in the mortality of T. castaneum. Among the studied species, C. sempervirens (France) with LC50 = 256.93 µL / L air had the highest fumigant toxicity (87.5%) on T. castaneum. Conclusion: Based on the insecticides, repellents and nutritional indices effect of Cupressus essential oils on T. castaneum they can be used as a biological management method for controlling storeroom pests.